The Effect of Training Methods and Eye-Foot Coordination On Football Dribbling Ability - Laksono, David Armando; Rachman, Hari Amirullah (Department of Physical Education, Sport, Health and Recreation, 2020)
This research aimed to examine: (1) the difference in the effect of acceleration and interval sprint dribbling methods; (2) the difference in the effect between high and low coordination towards; and (3) the interaction between training methods and coordination of football dribbling. This research is an experiment with a 2 x 2 factorial design. The coordination instrument is Soccer Wall Test while the dribbling instrument is Short Dribbling Test. The data were analysed using ANAVA. From this research, it can be concluded that (1) there is a significant difference in the effect between acceleration and interval sprint dribbling training methods on dribbling ability; (2) there is a significant difference in the effect between high and low coordination ability on dribbling ability; and (3) there is a significant interaction between training methods and coordination of football dribbling ability.